Implementation of a Management Information System (MIS) to Improve the Efficiency of Student Data Management in Vocational High Schools - Hanjas Prasetya (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2026)
This study aims to analyze and implement a Management Information System (MIS) to enhance the efficiency of student data management at SMK Bakti Karya Vocational High School. The primary challenge identified is the inadequate efficiency in student data management, which has been conducted manually, resulting in time-consuming processes and potential errors in data recording and processing. The research methodology employed is a system development approach utilizing the System Development Life Cycle (SDLC) framework, encompassing requirements analysis, system design, implementation, and testing phases. The research findings demonstrate that MIS implementation significantly improves student data management efficiency. The developed system successfully automates new student registration processes, academic data management, financial administration, and student data reporting. System testing reveals that data processing time decreased by 70% compared to the previous manual system. Furthermore, data accuracy increased substantially while reducing recording errors. The MIS implementation facilitates real-time access to student information for school personnel and streamlines the generation of required reports. The study concludes that MIS implementation proves effective in enhancing student data management efficiency and can be recommended for adoption in other educational institutions. The system's capacity to automate administrative processes, improve data accuracy, and provide real-time information access demonstrates its significant contribution to educational administration modernization.